Precompetitive anticipatory stress response of elite wrestlers - Farkas, G.; Bretz, E.; Barna, T.; Bretz, K. (International Journal of Wrestling Science, 2019)
We investigated the Hungarian national wrestling team`s anticipatory stress response for highlighted tournament in 2018 in October at the World Wrestling Championship in Budapest. We compared the results with the baseline data's what we measured one month before the WC. At the day of the competition when the wrestlers preparing for the fight it means that the vegetative nervous system`s sympathetic part is activating. This is the Canon stress. The heart rate is higher and steady the muscular strength is increase thanks for the stress. Why? Determinants of Sport Performance associated with the risk of Injury.